Capillary electrophoresis-laser-induced fluorescence (CE-LIF)-based immunoassay for quantifying antibodies against cyclic citrullinated peptides - Binh Thanh Nguyen; Park, Min; Yoo, Young Sook; Kang, Min-Jung (Royal Society of Chemistry, 2018)
We developed an assay for diagnosing rheumatoid arthritis (RA) by capillary electrophoresis with the laser-induced fluorescence detection (CE-LIF) of antibodies against cyclic citrullinated peptides (CCPs) using fluorescein isothiocyanate-labeled F-CCP11A and F-CCP. The CCPs were incubated overnight with a purified antibody against CCP and then injected into the CE-LIF system to estimate complex concentration. The immunocomplexes and free peptides were separated within 5 min, the LOD and LOQ values of the immunoassay are 0 1 mu g mL(-1) and 0 3 mu g mL(-1), respectively. The calibration curves for the immunocomplex had a coefficient of determination of 0.98. The reproducibility of the CE-LIF based immunoassay when using F-CCP11A and F-CCP was less than 5% and the accuracy ranged between 89 and 103%. The applicability of the assay was evaluated using serum samples from RA patients and healthy control subjects. We found that the sensitivity and specificity for RA diagnosis were 100% and 83.3%, respectively, for F-CCP11A and 100% and 90%, respectively, for F-CCP. These results demonstrate that the CE-LIF method can be useful for quantitative immunoassay development.